Pengembangan Inovasi Pelayanan Pembayaran Pajak Kendaraan Bermotor Tahunan di SAMSAT Surabaya Timur - Nayani Alya Aquila Muzdalifah; Diana Hertati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Surabaya is the city with the most vehicles in East Java Province. At the time of service, it is not uncommon to find people queuing and service hours coinciding with working hours which causes people to have to ask for permission. An innovation is needed that allows SAMSAT officers to come directly to the relevant office so that people do not need to ask permission to pay annual vehicle taxes at SAMSAT through the service innovation PAK LEMAN (Vehicle Tax Payment SAMSAT Manyar Delivery Service) based on delivery service with a ball pick-up method that serves at the agreed taxpayer location at SAMSAT East Surabaya. This research uses a qualitative method of case study approach. Data collection techniques through interviews, observation, and documentation. This study aims to analyze the innovation of PAK LEMAN delivery services in annual motor vehicle tax payments at SAMSAT East Surabaya which are analyzed using the theory of innovation attributes according to Rogers, namely 1) Relative Advantage, 2) Compatibility, 3) Complexity, 4) Triability, and 5) Observability. The results showed that the innovation of annual motor vehicle tax payments through the PAK LEMAN delivery service innovation has gone well, although there is still one innovation attribute that still needs attention such as the complexity innovation attribute.